next up previous index
Next: Sum of Poisson independent Up: Sums of Random Variables Previous: Sums of Random Variables

Discrete CAse


\begin{displaymath}\{Z=z\}= \cup_{k=0}^\infty ((X=k),(Y=z-k))\end{displaymath}

Since the events are disjoint we just sum their probabilities:

\begin{displaymath}P(Z=z)=\sum_{k=0}^\infty P(X=k) \dot P(Y=z-k)\end{displaymath}

Definition: For X and Y two random variables with mass distribution functions m1 and m2, the convolution of m1 and m2 is the distribution function m3 denoted m1*m2 given by:

\begin{displaymath}m_3(j)=\sum_k m_1(k) \dot m_2(j-k)

m3 is the distribution function of the random variable X+Y.

This operation is commutative and associative. We use induction to find the distribution of the sum of n random variables. Suppose that Sk is the sum of k dice:


See another example for the distribution of the sum of points in a bridge hand.


Susan Holmes